2021
DOI: 10.1177/2158244020988733
|View full text |Cite
|
Sign up to set email alerts
|

Social Return on Investment (SROI) to Assess the Impacts of Tourism: A Case Study

Abstract: This article contributes to the debate on the social and economic impacts generated by tourism activities using a methodology that is still insufficiently explored in the field of tourism and the impacts that this causes: social return on investment (SROI). Using the analysis of a case as a guiding thread, this article shows how the application of this methodology allows one to know in depth the social value that an emblematic palace (one of the main tourist attractions of a city in the south of Spain that was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
8
0
1
Order By: Relevance
“…Keberadaan Safari Lagoi diatur melalui Peraturan Menteri Kehutanan Republik Indonesia No: P.31/Menhut-II/2012 tentang Lembaga Konservasi sebagai suatu Lembaga Konservasi. Sebagaiamana tercantum Undang-Undang, maka peran Safari Lagoi yang sangat penting adalah turut melestarikan flora (tumbuhan) maupun fauna (satwa) [6]. Dengan demikian, Safari Lagoi menjalankan dua peran sekaligus yaitu sebagai peran konservasi serta menjadi obyek wisata di kawasan terpadu Bintan Resort.…”
Section: Pendahuluanunclassified
“…Keberadaan Safari Lagoi diatur melalui Peraturan Menteri Kehutanan Republik Indonesia No: P.31/Menhut-II/2012 tentang Lembaga Konservasi sebagai suatu Lembaga Konservasi. Sebagaiamana tercantum Undang-Undang, maka peran Safari Lagoi yang sangat penting adalah turut melestarikan flora (tumbuhan) maupun fauna (satwa) [6]. Dengan demikian, Safari Lagoi menjalankan dua peran sekaligus yaitu sebagai peran konservasi serta menjadi obyek wisata di kawasan terpadu Bintan Resort.…”
Section: Pendahuluanunclassified
“…Lozano-Oyola et al [61] adopted a practical approach, designed for use by local agents in order to boost destination sustainability, developing a system of compound indicators that would be simple to apply, measure and interpret. Ariza et al [22] concluded that analyzing tourism activity indicators could contribute to providing stakeholder solutions for addressing the positive and negative social impacts of tourism.…”
Section: Sustainability and Impact Indicatorsmentioning
confidence: 99%
“…As for the method's practical application for public administrations, Ruiz-Lozano et al [65] analyzed its utility in the assessment of subsidy applications based on social criteria. However, despite its unquestioned utility for the sector, to date, very few studies have considered the application of SROI in tourism [22].…”
Section: Social Value and Measuring Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Translating them it into monetary values allows for the assessment of their impact, making it a practical tool for any organization or project, regardless of its sector (educational, institutional, third sector, business, etc.) [6]. Also, by having qualitative and quantitative information, communication is very graphic, which helps to better transfer the work done [6].…”
Section: The Introductionmentioning
confidence: 99%